Implementation of Canva Assisted Problem-Based Learning Model for Education as an Effort to Increase Review Writing Skills - Septiani, Pramudita; Suharto, V. Teguh; Sudarwati, Sudarwati (CV. Tripe Konsultan, 2023)
This study aims to describe and explain the effect of the Canva-assisted problem-based learning model for education to improve the review writing skills of class XI A4 students of SMA N 3 Taruna Angkasa Madiun-East Java-Indonesia. The method used in this research is a class action research method which consists of 4 components, namely: (1) planning, (2) acting, (3) observing, and (4) ) Reflection (Reflecting). Data collection techniques are carried out utilizing observation, testing, and documentation. While the data analysis technique used is qualitative and quantitative data analysis. Qualitative data analysis pays attention to data selection (data reduction), describes data, and concludes. Furthermore, quantitative data, namely in the form of numbers, which includes student test scores, percentages, and scores, was then analyzed descriptively. The results of this study are: 1) The Problem-Based Learning model assisted by Canva for Education is very effective in improving the ability to write reviews of class XI A4 students of SMA N 3 Taruna Angkasa Madiun. 2) The results of using the Canva-assisted Problem Based Learning learning model for Education show significant results. After taking action the percentage of completeness of students which initially was only 33.33% or only 10 students who completed during the pre-cycle, increased in cycle I with a percentage of 50% or as many as 15 students completed, and increased again in cycle II with a percentage of 83.16%. or as many as 24 students complete. This indicates a significant increase from previously only 10 students who completed it to 24 students who completed it.